Pengaruh Penerapan Chronic Condition Self-Management (CCSM) terhadap Kepatuhan Pengobatan Pasien Hipertensi Peserta Prolanis BPJS di Malang Jawa Timur - Lilis Sulistiya Nengrum; Angga Setya Wahyudi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Hypertension is often called the silent killer because most people do not realize that he had hypertension. The success of the treatment is not only influenced by the quality of health services, attitudes/skills of its officers, the pattern of life of patients and their families but also influenced by patient adherence to treatment. Chronic Condition Self-Management (CCSM) is a guideline that was developed to help nurses, and health professionals on the client facilitate self-management of chronic conditions by providing a framework for effective interaction and management strategies. This study aims to determine the effect of the application of CCSM on treatment compliance. This research was conducted in the DPS dr. Suhartatik Gondang Legi in February - July 2017. The study design used was Quasi-Experimental, with pre-test and post-test with one group design. Total population 35 with a sample of 20 respondents into an intervention group, with a technique purposive sampling. The dependent variable is CCSM and independent variable and treatment compliance. Instruments using a checklist sheet and medication adherence questionnaire sheet. Based on statistical test paired t-test showed the p-value 0.000 (p <0.05), it can be concluded that there is a significant effect of the application of CCSM on treatment compliance. Based on these results, it is expected the nurse can useCCSM as a health promotion program to improve medication adherence in patients with chronic hypertension.